Generation of Decoy Signals Using Optical Amplifiers for a Plug-and-Play Quantum Key Distribution System - Woo, Min Ki; Park, Chang Hoon; Kim, Sangin; Han, Sang Wook (Applied Sciences (Switzerland), 2022)
In most quantum key distribution (QKD) systems, a decoy-state protocol is implemented for preventing potential quantum attacks and higher mean photon rates. An optical intensity modulator attenuating the signal intensity is used to implement it in a QKD system adopting a one-way architecture. However, in the case of the plug-and-play (or two-way) architecture, there are technical issues, including random polarization of the input signal pulse and long-term stability. In this study, we propose a method for generating decoy pulses through amplification using an optical amplifier. The proposed scheme operates regardless of the input signal polarization. In addition, a circulator was added to adjust the signal intensity when the signal enters the input and exits the QKD transmitter by monitoring the intensity of the output signal pulse. It also helps to defend against Trojan horse attacks. A test setup for the proof-of-principle experiment was implemented and tested, and it was shown that the system operated stably with a quantum bit error rate (QBER) value of less than 5% over 26 h using a quantum channel (QC) of 25 km.
Keywords: decoy-state protocol; information security; plug-and-play quantum key distribution; QKD; quantum communication; quantum optics